MIRERC 049/2025: An Assessment of The Enabling Environment for Inclusive Urban Sanitation In Nakuru City; Policies, Institutions, Financing, and Service Delivery - Mwende, Emmah; Dr Joy Nyawira Riungu; Dr Kirimi Lilian Mukiri (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Despite great progress in improving global sanitation, billions of people still lack access to safe sanitation. In 2022, only 17 countries were on track to achieve universal access by 2030, 84 countries were progressing too slowly and coverage in 24 countries was decreasing. This underscores the persistent challenge in achieving Sustainable Development goal 6.2, which is highlights the importance of safely managed sanitation. In Kenya, urban areas and cities like Nakuru City face critical gaps in sanitation infrastructure and enabling environments necessary for sustainable service delivery. Therefore, this research addresses these challenges by undertaking an assessment of the enabling environment for inclusive urban sanitation service delivery a case of Nakuru City The study is guided by four objectives which are to; examine the influence of the policy framework on inclusive urban sanitation service delivery in Nakuru City; assess the influence of institutional framework on inclusive urban sanitation service delivery in Nakuru City; describe the influence of financial models on inclusive urban sanitation service delivery in Nakuru City; assess the influence of service delivery approaches on inclusive urban sanitation service delivery in Nakuru City. A descriptive cross-sectional research design that proposes to integrate quantitative and qualitative methods of data collection and analysis will be adopted. The population is 110 participants consisting of county government staff, water utility staff, national agency and ministry staff, non-governmental organisations (NGOs), service providers, finance institutions, private sector actors, and community leaders. Out of which 86 respondents will be recruited into the sample using stratified random sampling method. Thereafter, non-probability methods including purposive and convenience techniques along with snowball sampling will be used to recruit the key informants. The inclusion of these diverse respondents is justified by their direct involvement in sanitation service delivery, policy-making, and implementation within Nakuru City. Data will be collected through questionnaires, document analysis, observation, and key informant interviews. Quantitative data from the questionnaire and structured observation checklist will be analyzed by the statistical package for the social sciences (SPSS) version 26 and this will consist of count and frequency distributions, mean, and standard deviation. Qualitative data from key informant interviews will be analysed by thematic analysis while content analysis will be done for observation and document data. Quantitative findings will be presented in tables, while qualitative data will be summarized narratively.